What About OCRG and its Support of Kato, Tolmach, and Wolf? - Oxnard Citizens for Responsible Government:::::: (1974)
A paper created by the Oxnard Citizens for Responsible Government explaining their endorsement of Kato, Tolmach, and Wolf for Oxnard City Council. Includes a summary of financial statements of candidates in the elections.